Correlations Between Cognitive Functions and Clinical Symptoms in Adolescents With Complex Post-traumatic Stress Disorder - Shin, Yee Jin; Kim, Sun Mi; Hong, Ji Sun; Han, Doug Hyun (Frontiers in Public Health, 2021)
Introduction: Complex post-traumatic stress disorder (C-PTSD) is characterized by the typical symptoms of PTSD, in addition to affective dysregulation, negative self-concept, and disturbances in interpersonal relationships. Children and adolescents with C-PTSD have been reported to have deficits in emotional and cognitive functions. We hypothesized that the following are associated with the severity of C-PTSD symptoms: (1) adolescents with C-PTSD who show deficits in emotional perception and cognitive functions, including executive function and attention; and (2) deficits in neurocognitive functions. Methods: Information on 69 adolescents with PTSD, aged 10–19 years, was gathered from seven shelters. All participants were assessed using complete clinical scales, including the C-PTSD Interview and Depression, Anxiety, and Stress Scales, and neurocognitive function tests, including the emotional perception, mental rotation, and modified Tower of London tests. Results: Adolescents with C-PTSD were more likely to have a history of sexual assault, dissociation, and self-harm than those with PTSD. The total and subscale scores of the C-PTSD Interview Scale in adolescents with C-PTSD were higher than that in adolescents with PTSD. In addition, neurocognitive functions, including emotional perception, attention, and working memory, were correlated with the severity of C-PTSD symptoms. Discussion: Adolescents with C-PTSD experienced more serious clinical symptoms and showed more deficits in neurocognitive functions than adolescents with PTSD. Clinicians should pay careful attention toward the emotional and neurocognitive functions when assessing and treating patients with C-PTSD.